RFID e suas aplicações na logística - França, Paula Gouveia de Andrade (2025)
The importance of logistics and technological advancement in operations management is addressed, with a focus on RFID. This tool is presented as a solution to improve the tracking of objects and products, providing information for better control and monitoring of them. The methodology used is bibliographical research where articles relating to the topic were analyzed, with a qualitative approach to understand in depth the subject discussed in the article. The functioning of the RFID system is explored, including its components, its functioning and its possible applications in logistics. There are discussions about the benefits generated by using this system, with greater visibility in the supply chain, operational efficiency and cost reduction, and also about the difficulties and barriers to implementing this tool within companies. With all the points covered, RFID technology is a promising tool for optimizing logistics processes, where it can improve efficiency and reduce costs in companies.